Anmeldelser - Holme Hansen, Thomas (Danish Yearbook of Musicology, 2005)
Review of: James R. Cowdery, Zdravko Blazˇebovic´, and Barry S. Brook (eds.): Speaking of Music: Music Conferences, 1835-1966. RILM Retrospective Series, 4; New York: Répertoire International de Littérature Musicale, 2004.